Proceedings of the 2005 Particle Accelerator Conference
DOI: 10.1109/pac.2005.1591748
|View full text |Cite
|
Sign up to set email alerts
|

Surface Study of Nb/Cu Films for Cavity Deposition by ECR Plasma

Abstract: Niobium (Nb) thin film deposited on copper (Cu) cavities through electron cyclotron resonance (ECR) plasma appears to be an attractive alternative technique for fabricating superconducting radio frequency cavities to be used in particle accelerators. The performance of these obtained Nb/Cu cavities is expected to depend on the surface characteristics of the Nb films. In this report, we investigate the influence of deposition energy on surface morphology, microstructure, and chemical composition of Nb films dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Those samples were produced by a small independent ECR plasma coating system. Tc and RRR measurements and the surface study results from TEM, SEM, SIMS and 3-D profilometry have been reported [10] and will be updated [11] seperately. The RF surface impedance of small samples are to be measured on a TE011 cavity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Those samples were produced by a small independent ECR plasma coating system. Tc and RRR measurements and the surface study results from TEM, SEM, SIMS and 3-D profilometry have been reported [10] and will be updated [11] seperately. The RF surface impedance of small samples are to be measured on a TE011 cavity [12].…”
Section: Introductionmentioning
confidence: 99%